Polymeric nanoparticle-based photodynamic therapy for chronic periodontitis in Vivo - de Freitas, Laura Marise [UNESP]; Calixto, Giovana Maria Fioramonti [UNESP]; Chorilli, Marlus [UNESP]; Giusti, Juçaíra Stella M.; Bagnato, Vanderlei Salvador; Soukos, Nikolaos S.; Amiji, Mansoor M.; Fontana, Carla Raquel [UNESP] (MDPI, 2016)
Antimicrobial photodynamic therapy (aPDT) is increasingly being explored for treatment of periodontitis. Here, we investigated the effect of aPDT on human dental plaque bacteria in suspensions and biofilms in vitro using methylene blue (MB)-loaded poly(lactic-co-glycolic) (PLGA) nanoparticles (MB-NP) and red light at 660 nm. The effect of MB-NP-based aPDT was also evaluated in a clinical pilot study with 10 adult human subjects with chronic periodontitis. Dental plaque samples from human subjects were exposed to aPDT—in planktonic and biofilm phases—with MB or MB-NP (25 μ/mL) at 20 J/cm2 in vitro. Patients were treated either with ultrasonic scaling and scaling and root planing (US + SRP) or ultrasonic scaling + SRP + aPDT with MB-NP (25 μ/mL and 20 J/cm2) in a split-mouth design. In biofilms, MB-NP eliminated approximately 25% more bacteria than free MB. The clinical study demonstrated the safety of aPDT. Both groups showed similar improvements of clinical parameters one month following treatments. However, at three months ultrasonic SRP + aPDT showed a greater effect (28.82%) on gingival bleeding index (GBI) compared to ultrasonic SRP. The utilization of PLGA nanoparticles encapsulated with MB may be a promising adjunct in antimicrobial periodontal treatment.
Keywords: Biofilms; Methylene blue; Nanoparticles; Periodontitis; Photodynamic therapy; PLGA